HISTORY OF KARSHI MAHALLAS (Archive of Conferences, 2021)
This article provides a comparative analysis of the various names, locations, and functions of the ancient neighborhoods of Karshi, one of the largest cities in Central Asia, ancient and modern, a symbol of peace and tranquility, based on written and ethnographic research.